Insulin Resistance in young obese females with and without Polycystic Ovary Syndrome. - Shehzad, Maheen; Abdul Sattar, Naila; Ishaq, Nadia (International Journal of Endorsing Health Science Research, 2022)
Background: The present study intends to determine the comparative insulin resistance (IR) among young obese females with and without polycystic ovary syndrome (PCOs) using the Homeostatic Model Assessment of Insulin Resistance (HOMA-IR). Methodology: During this comparative cross-sectional study, a total of 300 young obese females were evaluated for the presence of PCOS and insulin resistance. Based on the PCOs diagnosis, 250 obese PCOs females were included in group 1, and group 2 comprised 50 obese non-PCOs females. With the demographic details, patients' diabetic and lipid profiles were also evaluated, and the difference in the inference between the groups was drawn using SPSS version 22.0. Results: It is to note that more than 90% of the young obese PCOs females were diagnosed with type 2 diabetes mellitus (T2DM) while none of the obese non-PCOs females had diabetes. Furthermore, the HOMA-IR score was significantly high among young obese females diagnosed with PCOs (16.30 ± 1.62) as compared to those without PCOs (3.47 ± 0.37) (p<0.01). Conclusion: It is concluded from the study results that young obese females with PCOS are more prone to develop insulin resistance than those without PCOs.